Pengaruh Collectivism, Herding Behavior dan Pemahaman Akuntansi terhadap Intensi Pengimplementasian SAK EMKM - Puspa Rini; Eka Fauzihardani (Universitas Negeri Padang, 2022)
This study aims to examine the effect of collectivism, herding behavior and accounting understanding on intention to implementation SAK EMKM. This type of research is classified as survey research with a quantitative approach. The population in this study were SMEs manager in Dumai City, Indonesia. The research sample was determined by purposive sampling method. The amount of samples in this study was 80 respondents. The statistic testing result showed that collectivism have no effect on intention to implementation SAK EMKM, but variable herding behavior and accounting understanding have positive significant effect on intention to implementation SAK EMKM.